Contrasting the quality traits of aged bolar blade, topside and striploin cuts sourced from dark cutting and control Australian beef carcasses. (March 2019) - Holman, Benjamin W.B.; Hopkins, David L.
Abstract: The bolar blade, striploin and topside cuts from dark cutting (DC) and normal (nDC) beef carcasses were compared in terms of their eating quality, oxidation and colour traits. Carcass grades were assigned so that striploins assessed to have pH > 5.7 were classified DC. Cuts were aged (14 and 28 d) before their shear force, sarcomere length, ultimate pH, particle size, TBARS, drip and cooking losses, and colour stability traits were analysed. DC effects on tenderness traits were not uniform across all cuts. Only TBARS was influenced by grade and ageing period interactions. Colorimetric variation due to grade was more evident in the striploin than the other cuts, although this was independent to ageing or display. Cuts themselves differed and were impacted by ageing and display periods. It was concluded that unlike the topside and striploin, the bolar blade from DC carcasses had comparable quality to nDC and could therefore retain its value if priced independent to the entire carcasses.